Functional significance of M-type potassium channels in nociceptive cutaneous sensory endings - Passmore, Gayle M.; Reilly, Joanne M.; Thakur, Matthew; Keasberry, Vanessa N.; Marsh, Stephen J.; Dickenson, Anthony H.; Brown, David A. (Frontiers in Molecular Neuroscience, 2012)
M-channels carry slowly activating potassium currents that regulate excitability in a variety of central and peripheral neurons. Functional M-channels and their Kv7 channel correlates are expressed throughout the somatosensory nervous system where they may play an important role in controlling sensory nerve activity. Here we show that Kv7.2 immunoreactivity is expressed in the peripheral terminals of nociceptive primary afferents. Electrophysiological recordings from single afferents in vitro showed that block of M-channels by 3 µM XE991 sensitised Adelta- but not C-fibres to noxious heat stimulation and induced spontaneous, ongoing activity at 32ºC in many Adelta-fibres. These observations were extended in vivo: intraplantar injection of XE991 selectively enhanced the response of deep dorsal horn neurons to peripheral mid-range mechanical and higher range thermal stimuli, consistent with a selective effect on Adelta-fibre peripheral terminals. These results demonstrate an important physiological role of M-channels in controlling nociceptive Adelta-fibre responses and provide a rationale for the nocifensive behaviours that arise following intraplantar injection of the M-channel blocker XE991.